Neutrosophic Logic to Navigate Uncertainty of Security Events in Mexico - Mohammad Saif Wajid; Hugo Terashima-Marin; Mohd Anas Wajid; Florentin Smarandache; Satya Bhushan Verma; Mohammad Kaif Wajid (Neutrosophic Sets and Systems)
A significant degree of uncertainty surrounds security events in Mexico because of the interaction of multiple socioeconomic and political elements. Conventional probabilistic and logical approaches frequently fall short of properly handling this uncertainty. To effectively navigate and manage security incidents in Mexico, this study suggests applying neutrosophic logic, an extension of classical logic that allows for indeterminacy and partial knowledge. Neutrosophic logic provides a more adaptable framework for making decisions in uncertain contexts by simultaneously handling true, false, and indeterminate values. In this study, we have created a neutrosophic-based model that includes metrics like social unrest, economic instability, and crime rates to provide a thorough evaluation of the security environment. When the model is put to the test using actual data from different parts of Mexico, it outperforms conventional techniques in terms of prediction and interpretation of security occurrences. The findings demonstrate how neutrosophic logic helps security analysts and policymakers make more thoughtful and nuanced judgments by offering insightful information about the ambiguous nature of security occurrences. The ability to foresee and address possible risks is much improved when neutrosophic logic is incorporated into security event analysis. This not only improves overall security management but also creates new opportunities for its application in other sectors where uncertainty is crucial.